NGOs and the Blogs: Greek civil society’s role in a time of crisis - Veikou, Mariangela (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
This paper deals with the role of Greek NGOs in the field of migration today, as portrayed by new media platforms (blogosphere). The article identifies main lines of NGOs action as seen in the agenda of blogs which reflect issues that come to the fore with a focus on resource competition, social impact and values in a Greek society greatly hit by the crisis with consequences that impact the Greek civil society as a whole.